The Application of CRISPR-Based Genetic Engineering for the Elimination of Harmful Inherited Diseases in Human Embryos - Eka Cahya Muliawati (Science Journal Get Press, 2026)
CRISPR-Cas9 genome editing offers a theoretical approach for preventing inherited diseases by correcting pathogenic mutations at the embryonic stage. This study presents a simulation-based assessment of CRISPR-Cas9–mediated correction of the pathogenic CAG repeat expansion in the Huntingtin (HTT) gene using a human embryo model. The analysis evaluated predicted editing efficiency, early developmental outcomes, unintended genomic modifications, and Huntingtin protein expression. Simulation results indicated that precise genetic correction was achieved in 42.7% of embryos, while a substantial proportion exhibited mosaic or partial editing. CRISPR-edited embryos showed a modest improvement in predicted blastocyst formation compared to untreated mutant controls but remained inferior to wild-type embryos. Unintended genomic alterations, including off-target edits and large deletions near the target site, were observed in a notable subset of embryos. Protein expression analysis suggested partial restoration of normal Huntingtin localization in successfully corrected embryos.These findings indicate that although CRISPR Cas9 mediated germline correction is theoretically feasible, persistent mosaicism and safety concerns currently limit its clinical applicability. Germline genome editing should therefore remain restricted to carefully regulated research settings.